Chapter 2 The long road to Almanya Comics in language education for "guest workers" in West Germany, 1970s-1980s - Kesper-Biermann, Sylvia (Taylor & Francis, 2023)
This article argues that Amalia Alvarez's comics album The Stories of Five Undocumented Women (2013), based on a collection of stories told by migrant women, and Daria Bogdanska's autobiographical comics album Wage Slaves (2016) can be regarded as feminist comics activism. They are examples of comics activism since the comics point to an essential topic in opposition to a controversial issue, namely, the treatment of migrant women. The comics' emphasis on the situation of migrant women also makes it relevant to regard them as feminist activism, since they have a performative potential to create change regarding politics and legislation. The stories can influence how readers formulate and communicate thoughts about themselves and others, and they can contribute to changing societal structures. The comics also show how it is possible to mobilise resistance, generate support networks, and create hope. By making and publishing the comics, Alvarez and Bogdanska give migrant women an opportunity to come to voice and talk back against their situation, as well as against people who just express pity instead of taking action.